Nueva era en la comunicación comercial audiovisual: el marketing viral - Del Pino, Cristina (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2008)
Actual advertising saturation which all the media are submitted to without exception, leads the advertiser to search for new ways to make the message get to the target audience. The companies are investing their budgets in new advertising formats far from conventionalism. In this marketing metamorphosis we may include other extremely effective display: «the viral marketing». «Viral marketing» is defined as a group of techniques that try to take advantage of the pre-existing social nets in order to increase the knowledge of the brand. It is a new version that has achieved surprising effects without big investments or hiring mass medias; a new manifestation of the genuine «word of mouth», advertising from mouth to mouth that spreads through the net and generate coverage by means of unusual stories. This advertising format is being commonly used to the fact of the saturation of actual advertising in conventional media, characterized by the massive presence of commercial messages.